Performance evaluation of the IEEE 802.11n random topology WLAN with QoS application - Ziyad Khalaf Farej; Mustafa Mohammad Jasim (Institute of Advanced Engineering and Science, 2020)
The IEEE 802.11n supports high data rate transmissions due its physical layer Multiple Input ‎Multiple Output (MIMO) advanced antenna system and MAC layer enhancement features (frame ‎aggregation and block acknowledgement). As a result this standard is very suitable for multimedia ‎services through its Enhanced Distributed Channel Access (EDCA). This paper focuses on ‎evaluating the Quality of Service (QoS) application on the performance of the IEEE 802.11n ‎random topology WLAN. Three different number of nodes (3, 9 and 18) random topology with one ‎access point are modeled and simulated by using the Riverbed OPNET 17.5 Modular to ‎investigate the Wireless Local Area Network (WLAN) performance for different spatial streams. ‎The result clarified the impact of QoS application and showed that its effect is best at the 18 node ‎number topology. For a 4x4 MIMO, when QoS is applied and with respect to the no QoS ‎application case, simulation results show a maximum improvement of 86.4%, 33.9%, 52.2% and ‎‎68.9% for throughput, delay, data drop and retransmission attempts, respectively. ‎